Integrative Multiomics Analysis of the Heat Stress Response of Enterococcus faecium - Li Wang; Lin Qiao; Aike Li; Lixian Chen; Beibei He; Gang Liu; Weiwei Wang; Jun Fang (Biomolecules, 2023)
A continuous heat-adaptation test was conducted for one Enterococcus faecium (E. faecium) strain wild-type (WT) RS047 to obtain a high-temperature-resistant strain. After domestication, the strain was screened with a significantly higher ability of heat resistance. which is named RS047-wl. Then a multi-omics analysis of transcriptomics and metabolomics was used to analyze the mechanism of the heat resistance of the mutant. A total of 98 differentially expressed genes (DEGs) and 115 differential metabolites covering multiple metabolic processes were detected in the mutant, which indicated that the tolerance of heat resistance was regulated by multiple mechanisms. The changes in AgrB, AgrC, and AgrA gene expressions were involved in quorum-sensing (QS) system pathways, which regulate biofilm formation. Second, highly soluble osmotic substances such as putrescine, spermidine, glycine betaine (GB), and trehalose-6P were accumulated for the membrane transport system. Third, organic acids metabolism and purine metabolism were down-regulated. The findings can provide target genes for subsequent genetic modification of E. faecium, and provide indications for screening heat-resistant bacteria, so as to improve the heat-resistant ability of E. faecium for production.